Preservação do patrimônio documental fotográfico do arquivo histórico municipal de Erechim/RS: Juarez Miguel Illa Font - Ribeiro, Clarice (2017)
This research includes the Dissertation developed in the Professional Postgraduate Program in Cultural Patrimony of the Federal University of Santa Maria (PPGPPC-UFSM), and focused on the photographic collection of the Municipal Historical Archive of Erechim - RS. This file was founded in the year of 1980, ten years later, it was renamed Municipal Historical Archive Juarez Miguel Illa Font (AHM). Its main functions and attributions are: search, custody and conservation of the historical documentation of the municipality and allow the use of its collection for consultation to the general public. The purpose of this archive is to preserve the history of the municipality of Erechim and keep alive the memory of the people of Erechim. In this way, its documentary collection constitutes a documentary heritage of immeasurable historical / cultural value for the municipality and region. Among this heritage, a photographic collection is included, which represents an important role in the archival research, which justified the accomplishment of this research, whose objective is the production of a manual of procedures for the preservation of the AHM's photographic collection, aiming at their permanent access. For the theoretical and legal basis of the research, aspects related to its object were discussed, discussing the concepts of heritage and its conceptual bases, archival and photography. The research is applied in nature with a qualitative approach, and is characterized as descriptive from the point of view of its objectives. The research method is the case study, and data collection was defined as field research, since it constitutes the activity used to search for information that relates to the object of study, in this case, the documentary heritage of the AHM. For data collection, interviewing and direct observation at the site were used as techniques. As a result, we have a diagnosis of the general situation of the archive, and the contextualization of its photographic collection. These results, together with the archival theory and methodology, guided the construction of the procedures manual for the AHM photographic collection, the final product of this research. It is hoped that this manual will complement the work already developed in the archive, so that it can improve its preservation techniques, attempting to minimize actions that could jeopardize the useful life of the collections.